Creating the Arsenal: Augusta University's Undergraduate Research Journal. Issue 1 (1st May 2017) - Johnson, Melissa E.; Mears, Kim; Drescher, Abigail
ABSTRACT: The Center for Undergraduate Research (CURS) at Augusta University supports faculty-led undergraduate research. In collaboration with a student organization, the Program Coordinator of CURS contacted the Augusta University Libraries to investigate how to start an undergraduate research journal and identify a hosting venue. Two librarians provided guidance on the creation of a new Open Access journal using resources already provided by the university. This article discusses establishing the journal's identity, developing policies and processes, hosting and publishing the journal, as well as challenges faced throughout the process.